Highly sensitive flexible proximity tactile array sensor by using carbon micro coils - Nguyen, Tien Dat; Han, Hyo Seung; Shin, Hyeon-Yeong; Nguyen, Canh Toan; Phung, Hoa; Hoang, Hung Van; Choi, Hyouk Ryeol (Sensors and actuators. A. Physical., 2017)
•This novel dual mode array sensor described in this paper based on the effect of carbon microcoils (CMC) in soft dielectric elastomer substrate material over a flexible printed circuit electrode board (FPCB).•In the first, the sensor structure design and its properties are investigated.•Secondly, the tactile sensing, proximity sensing, and dual mode sensing performance are examined.•Next, the sensor signal processing for measuring inductance, capacitance, resistance, and impedance (LCRZ) will be analyzed.•We succussed to demonstrate the performance of 16×16 proximity tactile array sensor. Recently, the new generation of robotics, called soft robotics, are exploited by soft materials as the revolutionary tools which innovate the current challenges. In this paper, we propose a novel dual mode array sensor based on the carbon microcoils (CMC) in soft dielectric elastomer substrate material. It can detect the distance to the object as well as the pressure when it has contact. In the first, the design of sensor structure and its properties are investigated. Various experiments are performed on the dielectric substrates, electrode structures, and the target objects by changing electrical impedance formed by CMC under the alternating current (AC) excitation voltage with the dominant excitation frequency at 100kHz. Secondly, the tactile sensing, and proximity sensing, that is dual mode sensing performance are examined with respect to repeatability, reversibility, durability, sensitivity, and hysteresis. In the next, the sensor signal processing for measuring impedance (LCR) are analyzed with an analog signal processing, analog switching circuit, and digital processing. Finally, we successfully demonstrate the performance of 10×10 proximity tactile sensor which is capable of detecting a 30mg (300mgF) droplet and applied pressure up to 330kPa approximately, and detected the distance of the metal object from 150mm to touch on to the CMC sensor surface. Moreover, the 16×16 multi-cell arrays tactile sensor with 2mm electrode pads spatial-resolution activated in 32mm×32mm×0.6mm is performed to show the high resolution performance as well as multiple touches on independent cells.